Design of Close-Fit Liners for the Rehabilitation of Gravity Pipes - Kampbell, Norman E.; Simicevic, Jadranka (American Society of Civil Engineers, 2021)
"MOP 145 provides a comprehensive explanation of the design of flexible, close-fit linings for the renewal or rehabilitation of pipes designed for gravity flow such as sanitary sewers, culverts, and storm sewers"-- Provided by publisher.
"Prepared by the Pipeline Infrastructure Committee of UESI."
Keywords: Water-pipes -- Lining -- Design and construction.; Sewage lagoons -- Linings -- Design and construction.; Sewer-pipe -- Sewer-pipe -- Maintenance and repair.; elektronické knihy; electronic books